Current approaches to improve the anticancer chemotherapy with alkylating agents: state of the problem in world and Ukraine - Iatsyshyna, A.P. (Вiopolymers and Cell, 2012)
Alkylating agents are frequently used in many established anticancer chemotherapies. They alkylate the genomic DNA at various sites. Alkylation of the guanine at the O6-position is cytotoxic, it has the strongest mutagenic potential, as well as can cause the tumor development. Alkyl groups at the O6-position of guanine are removed by the DNA repair enzyme O6-methylguanine-DNA methyltransferase (MGMT). The effectiveness of alkylating chemotherapy is limited by MGMT in cancer cells and adverse toxic side effects in normal cells. Different approaches consisting in the modulation of the MGMT expression and activity are under development now to improve the cancer chemotherapy. They include two main directions, in particular, the increase in chemosensitivity of cancer cells to alkylating drugs and the protection of normal cells from the toxic side effects of chemotherapy. This review is focused on current attempts to improve the alkylating chemotherapy of malignant tumours worldwide and state of the issue in Ukraine. Keywords: cancer chemotherapy, strategies of chemotherapy improvement, alkylating agents, O6-methylguanine-DNA methyltransferase (MGMT), DNA repair.